Adjuvant measures and genetic evaluations to improve results of hair transplantation - Fattah, Jalal Hamasalih (Cellular and Molecular Biology, 2022)
Follicular unit extraction (FUE) has evolved dramatically as the most recent advancement in surgical hair restoration as it leaves a tiny scar and creates natural and pleasing results. This study aims to show the effectiveness of adjuvant measures and genetic evaluations in improving outcomes. Prospective analysis of 271 male patients with androgenic alopecia who underwent hair transplantation with FUE technique between August 2015 and February 2020 at our center was conducted. The mean age was 35.93 ±4.40 years. At one year postoperatively, patients were asked to fill up a questionnaire which included their satisfaction level, need for 2nd session, and complications. Informed written consent was obtained from all patients. Also, blood samples were provided from patients before the operation. RNA extraction and cDNA synthesis were performed using the RNX-Plus kit (Cinnagen, Iran) and Vivantis kit (Malaysia). Amplification of SRD5A2 and GAPDH genes (as internal standard) for measuring gene expression was performed by real-time PCR. Data were analyzed using the statistical package for social science SPSS V. 23. In the last 156 cases, the addition of 40 mg of Triamcinolone to the LA solution led to a dramatic reduction of the incidence of postoperative oedema, from 40% to 9%. Adding three sessions of PRP at 2nd, 4th and 6th months postoperatively resulted in an increased patient satisfaction rate with better hair density and thickness where the rate of highly satisfied patients increased from 64.5% to 83.7%. The addition of 40 mg Triamcinolone to the LA solution was highly effective in reducing postoperative oedema. Three sessions of PRP at 2nd, 4th and 6th months postoperatively were recommended. The results of SRD5A2 gene expression showed that the expression of this gene in satisfied (P = 0.049) and dissatisfied (P = 0.028) patients were significantly higher than highly satisfied patients, which means that the SRD5A2 gene expression had an essential role in the successfulness of hair transplantation. The increased expression of this gene could reduce the response to hair transplantation.